RISK ASSESSMENT OF NITRAT CONTAMINATED IN GROUNDWATER IN GIAO THUY DISTRICT, NAMDINH PROVINCE, VIETNAM - Ly, Ha Thi Thu; An, An The; Nguyen, Ha Thi; Tran, Bang Nguyen (International Journal of Biosciences and Biotechnology, 2022)
Environmental pollution due to agricultural production activities, and the use of fertilizers and pesticides is a matter of great concern due to its harmful effects on the soil environment, water environment, and ecosystems. In this study, the risk of nitrate contamination in shallow groundwater related to agricultural land was evaluated using DRATIC and IPNOA models with 66 soil samples and 132 groundwater samples. The results showed that hazard was found at very low with HI values ranging from 3.5-6.06. The RI of nitrate-contaminated groundwater from agricultural activities is in the range of 539 - 1058. The assessment results show that the vulnerability index has a significant impact on the RI index, and areas with a high vulnerability index have a higher risk of groundwater pollution. The NO 3 - concentration seems to be stable, ranging from 0.02 to 0.11 mg/l, and all meet with the QCVN 09:2018/BNTMT for groundwater quality. No clear correlation between vulnerability factor and risk factor with NO 3 - concentration in groundwater.